Race, power, and the subprime/forceclosure crisis: A mesoanalysis - Gary A. Dymski; Jesus Hernandez; Lisa Mohanty (Levy Economics Institute of Bard College, 2011)
Economists' principal explanations of the subprime crisis differ from those developed by noneconomists in that the latter see it as rooted in the US legacy of racial/ethnic inequality, and especially in racial residential segregation, whereas the former ignore race. This paper traces this disjuncture to two sources. What is missing in the social science view is any attention to the market mechanisms involved in subprime lending; and economists, on their side, have drawn too tight a boundary for the economic, focusing on market mechanisms per se, to the exclusion of the households and community whose resources and outcomes these mechanisms affect. Economists' extensive empirical studies of racial redlining and discrimination in credit markets have, ironically, had the effect of making race analytically invisible. Because of these explanatory lacunae, two defining aspects of the subprime crisis have not been well explained. First, why were borrowers that had previously been excluded from equal access to mortgage credit instead super included in subprime lending? Second, why didn't the flood of mortgage brokers that accompanied the 2000s housing boom educe the proportion of minority borrowers who were burdened with costly and ultimately unpayable mortgages? This paper develops a mesoanalysis to answer the first of these questions. This analysis traces the coevolution of banking strategies and client communities, shaped by and reinforcing patterns of racial/ethnic inequality. The second question is answered by showing how unequal power relations impacted patterns of subprime lending. Consequences for gender inequality in credit markets are also briefly discussed.
Keywords: B50; G21; G28; J15; J16; P16; R31; 330; race; ethnicity; subprime mortgages; discrimination; redlining; foreclosures; power; mesoanalysis; Subprime-Hypothek; Finanzmarktkrise; Kreditmarkt; Ethnische Diskriminierung; Segregation; USA